APPLICATION OF IMPROVED WORKING EQUIPMENT OF A SINGLE- BUCKET EXCAVATOR IN EXCAVATING OPEN DRAINS. - Halimov Tilavjon; Safarov Shermurod; Amrullayev Timurbek; Hakimov Akobir (TADQIQOTLAR.UZ, 2024)
Annotation: The article presents the results of research on the development of improved working equipment for single-bucket excavators in the excavation of open channels and collectors, and based on the results of the research, a structural scheme of the machine was developed.